Glaucoma Profile in a Tertiary Eye Hospital of Bangladesh - Islam, Mohammad Ariful; Hel Azam, Amir Abdulla; Siraj, Md Shahjahan; Alam, Afroza E; Hasanuzzaman, Md; Bari Rasel, S M Shafiul (Eastern Medical College Journal, 2023)
Background: Glaucoma is a chronic progressive optic neuropathy associated with characteristic optic nerve damage which may lead to certain visual field loss patterns at least some part of which is due to a sub optimal intra ocular pressure. Glaucoma is also known as silent killer of vision. Objective: To evaluate the pattern of glaucoma among the patients who were presented to a tertiary eye hospital, in southern region of Bangladesh. Method: A prospective observational study was done in outpatient department (OPD) of a tertiary eye hospital from January 2019 to December 2019. All patients with glaucoma were included. Data on age at presentation, gender, laterality, intraocular pressure, cup/disk ratio (C:D) with neuroretinal rim (NRR) and diagnosis were collected from OPD. Patients in age of 1 day - 100 years were included in this study. Patients were grouped into three age groups (0-25 years, 26-50 years and >50 years) and grouped in terms of clinical diagnoses. Result: A total of 387 eyes of 292 patients were included. Primary angle closure glaucoma (PACG) was the predominant type (45%) followed by primary open angle glaucoma (POAG) (32%), secondary glaucoma (14%) and normal tension glaucoma (6%). Other types including juvenile glaucoma (2%) and congenital glaucoma (1%) were also present but of lower prevalence. Conclusion: Primary angle closure glaucoma (PACG) was the predominant form of glaucoma followed by POAG suggesting that the pattern in Bangladesh could be quite different from that reported for primary glaucoma in the Western literature. EMCJ. July 2022; 7(2): 16-20